CO-INOCULATION OF PHOSPHATE SOLUBILIZING BACTERIA AND RHIZOBIA FOR IMPROVING GROWTH AND YIELD OF MUNGBEAN (VIGNA RADIATA L.) - M. A. Qureshi; M. A. Shakir; A. Iqbal; N. Akhtar; A. Khan (Journal of Animal and Plant Sciences, 2011)
Four isolates each of Bacillus and Rhizobium sp were selected and characterized for their P-solubilization and auxin production. All the isolates produced auxin but with different degree of efficacy. The isolates of Rhizobium and Bacillus having maximum auxin production and P-solubilization were selected and further evaluated for improving growth, nodulation and yield of mungbean at two fertilizer levels (20-25 and 20-50 kg NP ha-1) in a pot experiment. Results revealed that inoculation significantly increased the growth and yield of mungbean as compared to uninoculated control. However, co-inoculation of R. phaseoli and B. megaterium further enhanced the mungbean growth, nodulation and yield in comparison with controls. Rhizobial inoculation produced 24.0 g pot-1 pod yield and 30.20 g pot-1 straw yield whereas co-inoculation produced 24.3 g pot-1 pod yield and 32.07 g pot-1 straw yield at highest fertilizer level. Co-inoculation produced higher root mass (231.3 g), root length (50.54 cm), nodule number (78) and nodular mass (0.216 g) as compared to control. Similarly, co-inoculations also improved the nutrient concentration in mung plant and grains as compared to control. Study suggested that co-inoculation with R. phaseoli and Bacillus sp. employed assenting effect on yield components and could be a useful approach than their sole application. However, a comprehensive approach to employ the PGPR in legumes should be carried out to explore the hidden potential of PGPR and to promote the quality and yield of crops under field conditions.
Keywords: Rhizobium; Bacillus; Co-inoculation; Phosphate Solubilizing Bacteria; mung bean